2023
DOI: 10.1108/itse-10-2022-0133
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation model based on procedural behaviors for predicting MOOC learning performance: students’ online learning behavior analytics and algorithms construction

Abstract: Purpose The purpose of this study is to set up an evaluation model to predict massive open online courses (MOOC) learning performance by analyzing MOOC learners’ online learning behaviors, and comparing three algorithms – multiple linear regression (MLR), multilayer perceptron (MLP) and classification and regression tree (CART). Design/methodology/approach Through literature review and analysis of data correlation in the original database, a framework of online learning behavior indicators containing 26 beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…For example, Rivas et al [30] used machine learning techniques to explore the relationship between students' learning behaviors and academic performance and proposed a machine learning-based framework for analyzing student performance. Tong et al [31] proposed a performance prediction assessment model for learning process behavior based on machine learning, and detailed the construction process and feature extraction method of the model. Yan et al [32] also suggested in their study that applying machine learning to learning behavior analysis has the following advantages: efficiency: machine learning can quickly analyze and mine large amounts of online learning data; automation: machine learning can automatically analyze and process online learning data without human intervention; personalization: machine learning can provide students with personalized learning resources and learning paths for students; predictive: machine learning predicts and evaluates students' learning behaviors and academic performance.…”
Section: Machine Learning Based Behavioral Sequence Analysis Methodsmentioning
confidence: 99%
“…For example, Rivas et al [30] used machine learning techniques to explore the relationship between students' learning behaviors and academic performance and proposed a machine learning-based framework for analyzing student performance. Tong et al [31] proposed a performance prediction assessment model for learning process behavior based on machine learning, and detailed the construction process and feature extraction method of the model. Yan et al [32] also suggested in their study that applying machine learning to learning behavior analysis has the following advantages: efficiency: machine learning can quickly analyze and mine large amounts of online learning data; automation: machine learning can automatically analyze and process online learning data without human intervention; personalization: machine learning can provide students with personalized learning resources and learning paths for students; predictive: machine learning predicts and evaluates students' learning behaviors and academic performance.…”
Section: Machine Learning Based Behavioral Sequence Analysis Methodsmentioning
confidence: 99%
“…There are other studies on predicting the risk of dropouts using log datasets [22]- [26]. In work by [22], weighted attributes are introduced prior to SVM Classifier, resulting in better performance than non-weighted attributes.…”
Section: A Literature Reviewsmentioning
confidence: 99%
“…DeepFM [25] is DNN and factorization machine hybrid, achieving 99% in validation data. In work by [26] multiple linear regression (MLR), multilayer perceptron (MLP) and classification and regression tree (CART) are compared with MLP and CART performing better than MLR. Other than predicting the risk of dropout, there are studies on using machine learning to predict graduation [27], [28][29] has created a mobile application with deep learning to enhance English and Arabic vocabulary among children.…”
Section: A Literature Reviewsmentioning
confidence: 99%